Implementation of the 2013 Curriculum in Islamic Religious Education Learning - Irine Dwi Widianingrum (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this study is to explore the implementation of the 2013 curriculum in PAI learning at SDN Singaraja 1 so that it is related to this researcher. This study uses qualitative research using analytical descriptive techniques. Data collection is carried out by interview, observation and documentation methods. The subjects of this study are Islamic Religious Education Teachers at SDN Singaraja 1 Indramayu. The results of the study indicate that the implementation of the 2013 curriculum in PAI learning gets optimal results, so teachers must be able to be motivators of students. (1) This study shows that the implementation of the 2013 curriculum in PAI learning at SDN Singaraja 1, the results in general have gone well starting from the preparation and evaluation stages, but there is one obstacle in the implementation of the 2013 curriculum, namely: (1) many teachers have not attended socialization/workshops related to the approach method, assessment and teaching techniques. (2) Lack of facilities and infrastructure. (2) The impact of this K13 has positive and negative impacts. For positive impacts, students become more active, independent, innovative, creative and follow technological developments. The negative impact is that it burdens students due to increased class hours, a lack of learning media, inadequate technology mastery, and inadequate information support for teachers.